Correlation between brain volume and retinal photoreceptor outer segment volume in normal aging and neurodegenerative diseases - Uchida, Atsuro (PLoS One, 2020)
PURPOSE: To investigate the association between outer retinal layer metrics, including photoreceptor outer segment volume, on spectral-domain optical coherence tomography (OCT) and brain volume on MRI in normal aging, Alzheimer’s disease and Parkinson’s disease. METHODS: This was an exploratory analysis of a cross-sectional cohort study that was approved by the Cleveland Clinic Institutional Review Board to evaluate neurodegenerative disorders. Subjects aged ≥ 50 were recruited. A comprehensive neurological exam, brain MRI with volumetric evaluation, and OCT were performed for each subject. Outer retinal layer parameters, including ellipsoid zone (EZ) to retinal pigment epithelium (RPE) volume (i.e., surrogate for panmacular photoreceptor outer segment volume), were evaluated with a novel OCT analysis platform. RESULTS: Of 85 subjects, 64 eyes of 64 subjects met MRI and OCT quality control criteria. Total brain volume (%ICV) significantly correlated with EZ-RPE volume in the normal cognition control group (n = 31, Pearson correlation coefficient 0.514, P < .01), the Parkinson’s disease group (n = 19, Pearson correlation coefficient 0.482, P = .04), and the Alzheimer’s dementia group (n = 14, Pearson correlation coefficient 0.526, P = .05). Multiple linear regression analysis revealed that photoreceptor outer segment (i.e., EZ-RPE) volume was an independent, influential factor on total brain volume in all study subjects (Coefficient 15.2, 95% confidence interval 7.8–22.6, P < .001). CONCLUSION: Outer retinal parameters on OCT may serve as a novel biomarker related to brain volume. This correlation was noted in control subjects suggesting a possible developmental link between retina and brain volume. This relationship was also maintained with atrophic neurodegenerative disorders. Further research is needed to explore possible threshold differences for underlying neurodegenerative disorders.